Sustainability of the Kawasan Rumah Pangan Lestari (A Sustainable Food House Area Program) in Pasuruan Regency - Khuswati, Ririn; Pudjiastuti, Agnes Quartina; Sumarno, Sumarno (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 1 (2022): Vol.16, No.1, 2022DO - 10.24843/SOCA.2022.v16.i01.p03, 2022)
The global demand for food is consistently increasing. However, the agricultural land area tends to decline in size. It would pose serious and strenuous issues in the future. The utilization of the house yard area through the Kawasan Rumah Pangan Lestari Program (KRPL/Sustainable Food House Area Program) offered a resolution for this issue. The objective of this study was to investigate the sustainability of the KRPL program in Pasuruan Regency from its ecological, social, and economic aspects, and most influential attributes. Interviews sessions arranged with 18 participants who funded by the National and Regional Revenues and Expenditures Budget. The data collected were analyzed using the Multi-Dimensional Scaling (MDS) approach and RAPFISH software. Findings revealed that the KRPL program classified into the moderate category, which indicated it could be executed sustainably in Pasuruan Regency. The economic aspect had the lowest sustainability index compared to the ecological and social aspects. The most influential attributes identified were the utilization of kitchen waste, pest control and irrigation (ecological), cooperation between group members, utilization of village nursery house, interests and benefits for other members (social aspect), cost savings, fulfillment of household consumption, user fees and visits, and product sales processed products (economic). To ensure the sustainability of the program, we need to address some issues and work in several areas: 1) community knowledge, attitudes, and skills improvement; 2) consumptive to productive thinking behavior transition; 3) intensive guidance from the creative and innovative workers, and 4) KRPL promotion